The effectiveness usage of ablution pool in mosque during the transition phase to endemic in Kepala Batas, Penang / Muhammad Syahmi Nizam and Salahuddin Abdul Hakeem Abas - Nizam, Muhammad Syahmi; Abas, Salahuddin Abdul Hakeem (2023)
Mosque is one of the places and great buildings where Muslims can gather and perform prayers together. Before performing a prayer, a Muslim have to take ablution. However, due to pandemic Covid 19 outbreak, the mosque was closed during Movement Control Order (MCO). Ablution pools were also closed to prevent the formation of a new cluster among the society's users, which would reduce the number of congregants. Even though the mosque is beginning to reopen during CMCO, the ablution pool remains closed. In fact, congregants were encouraged to do ablution at home before attending the mosque. However, ablution pools nowadays are reopened for users since Malaysia has entered a transition to an endemic phase. Therefore, the issue was the relevancy usage of ablution pool among congregants as whether there were congregations that still take precautionary measures and do not use ablution pool. Therefore, this study was conducted to analyse the preferences usage of the ablution pool and to analyse the effectiveness usage of the ablution pool in the mosque during the transition of endemic phases. Thus, several mosques in Kepala Batas, Penang were chosen to carry out this study and this research was applying both quantitative and qualitative methods. The finding of this research is that the use of ablution pools is no longer relevant today as congregants preferred to use a water tap as to take an ablution as it is more hygienic.